Food waste and byproduct valorization through bio-processing: Opportunities and challenges - Turon, Xavier; Venus, Joachim; Arshadi, Mehrdad; Koutinas, Michalis; Lin, Carol Sze Ki; Koutinas, Apostolis A. (My University, 2014)
The bioeconomy era will rely on efficient fractionation of renewable resources via integrated biorefineries. The food supply chain waste, despite its inherent variability, could evolve into an important industrial feedstock on account of its availability, versatility, and sustainability, for the production of bio-based products. Waste streams generated from all stages of the life cycle of food products could be refined into different fractions, which will be either purified to high-value molecules or converted via green chemical and/or biotechnological routes for the production of bio-based products. A working group of the EUBis COST Action TD1203 is taking steps to gather a critical mass of knowledge and expertise to create innovation and technological breakthroughs.
Keywords: Bio-based products; Bioprocessing; Biorefinery; Chemicals; Food supply chain waste